THE CONSTRUCT OF FEMININITY OF THE FEMALE'S MAIN CHARACTER IN THE THAILAND MOVIE "THE TEACHER'S DIARY" - Febriand, Fandra (International Review of Humanities Studies, 2021)
This article discusses the construct of femininity in the Thai film "The Teacher's Diary" (2014) through an analysis of the main female character. The film is a romantic-comedy genre directed by Nithiwat Tharathorn which tells the story of two teachers who both teach at the same floating school, however each teaching at different periods of time. Through a diary written by Ann (a female teacher) who first taught at the school, Song (a male teacher) learns a lot about how to deal with the face of the unideal teaching conditions in a floating school. Using gender concepts, namely femininity and masculinity as social constructions from Oakley and Gender Stereotype Characteristics from Kite, this paper argues that although it does not completely break away from gender stereotypes, Ann's femininity also shows masculinity in herself. The construction of Ann's femininity as a single Thai woman is also not completely against the patriarchal system. However, Ann's character offers a different perspective on how to be a single Thai woman.